Design and development of a 3-DOF robotic-assisted ankle rehabilitation device - Saysay, Romel S. (Animo Repository, 2020)
The purpose of this study is to develop a 3-DOF robotic-assisted ankle rehabilitation device to facilitate a more natural ankle movement during rehabilitation. With the ankle considered as one of the more complex joints in the body, it can rotate about all three anatomical axes of rotation and it is crucial for balance and propulsion during walking. However, disabilities and physical injuries to the ankle joint can severely affect normal daily tasks of standing and walking. Thus it is important to properly undergo physical rehabilitation which involves repetitive mobility and strengthening exercises to regain motor function. Currently, several robotic devices have been developed to assist in physical rehabilitation of the ankle. However, most designs only facilitate the dorsi-plantarflexion motion of the ankle which is just one of its three possible axes of rotation. In the design of the ankle rehabilitation device, the anatomy of the ankle is reviewed together with ranges of motion it can reach about each axes of rotation. Several types of ankle rehabilitation devices have been studied and it was concluded that an orthosis type is more accommodating to the user since it fits to the lower limb and the foot mimicking a therapist’s hands to deliver force evenly. The device uses a cable-driven mechanism that attaches to the foot and routed to an actuation unit through cable guides. This mechanism allows for the separation of the motors and other bulky components from the ankle. The main orthosis is based off a commercial ankle brace that ensures comfortable fit and easier attachment. A wooden mock ankle with a ball joint was used to simulate the 3-DOF movement of the ankle. Several experiments have been performed for validation such as if the device can reach the maximum angles, and if the GUI delivers calibrated movements. Overall, the design and development of a 3-DOF robotic-assisted ankle rehabilitation device was successful. This device design provides a new design concept to the current state of the art in robotic ankle devices that can facilitate a more naturalistic movement during therapy. The device also aims to ultimately be used in actual therapy of ankle disabilities and injuries to help both patients and therapists.